THE SOCIO-ECONOMIC SIGNIFICANCE OF MUSIC FESTIVALS ON THE EXAMPLE OF POL’AND’ROCK FESTIVAL (Research Bulletins of the Faculty of Economic Sciences, 2025)
The number of music festivals organized in the world is growing. These are events that attract a large group of participants, and have an impact not only in the social but also economic sphere. The aim of the research was to determine the socio-economic importance of music festivals in Poland using the Pol’and’Rock Festival as an example. The results were obtained using a survey using a questionnaire. The time scope of the research covers 2023. The article uses secondary sources (subject literature and Internet resources) and primary sources (results of the conducted research). As a result of the conducted research, the research hypothesis was confirmed, according to which, in relation to the organization of the Pol’and’Rock Festival, social factors such as integration, atmosphere and sharing passion are more important than economic factors such as local development, financial influence or recognition of the area.
Keywords: music festival, event and festival management, importance of events and festivals, Pol’and’Rock Festival